Biomembrane-Modified Field Effect Transistors for Sensitive and Quantitative Detection of Biological Toxins and Pathogens - Gong, Hua; Chen, Fang; Huang, Zhenlong; Gu, Yue; Zhang, Qiangzhe; Chen, Yijie; Zhang, Yue; Zhuang, Jia; Cho, Yoon-Kyoung; Fang, Ronnie H; Gao, Weiwei; Xu, Sheng; et al. (ACS nano, 2019)
The efforts of detecting bioactive targets with complex, dynamic, and unknown molecular profiles have inspired the development of various biosensor platforms. Herein, we report a cell-membrane-modified field effect transistor (FET) as a function-based nanosensor for the detection and quantitative measurement of numerous toxins and biological samples. By coating carbon nanotube FETs with natural red blood cell membranes, the resulting biomimetic nanosensor can selectively interact with and absorb broad-spectrum hemolytic toxins regardless of their molecular structures. Toxin–biomembrane interactions alter the local charge distribution at the FET surface in an ultrasensitive and concentration-dependent manner, resulting in a detection limit down to the femtomolar (fM) range. Accurate and quantitative measurements are enabled via a built-in calibration mechanism of the sensor, which overcomes batch-to-batch fabrication variations, and are demonstrated using three distinct toxins and various complex bacterial supernatants. The measured signals of bacterium-secreted proteins correlate linearly with the actual bacterial numbers, making the biosensor a nontraditional approach to rapidly detecting bacterial concentrations without a need to count bacterial colonies.